Thermoelectric Power Properties of Graphite‐Loaded Nitrile Rubber/Poly(vinyl chloride) Blends Above the Percolation Threshold. Issue 1 (17th June 2014) - Mansour, S.A.; Hussein, M.; Moharram, A.H.
ABSTRACT Electrical conductivity, thermoelectric power (TEP), and thermal measurements were used to characterize acrylonitrile butadiene rubber/poly(vinyl chloride) blends loaded with graphite above the percolation threshold as thermoelectric materials. Low thermal conductivities and high electrical conductivities accompanied with relatively high Seebeck coefficients lead to relatively high thermoelectric performances (ZT = 2.24 × 10−6). The TEP of composites is (9.5–16.2) μV/°C near room temperature. Two conduction mechanisms have been identified in composites above the percolation: the metallic‐like mechanism in the temperature range of 308–363 K and variable range hopping mechanism due to delocalized electrons at the Fermi level above 363 K. Using the values of the dc electrical conductivity and TEP, the values of the charge carrier concentration and the charge carrier mobility were calculated.